Odpowiedzi

2009-09-17T21:38:19+02:00
A) [(-2)×10-(-4)×5]×3-14÷(-2)= [-20-(-20)]x3+7=0X3+7=7

b) (-6)²÷(-4)+3×(-6)-[-(-8)]=36:(-4)-18-8=-9-18-8=-35

c)(16×3)÷(-8)-15÷(-3)+(-7)²=48:(-8)+5+49=-6+5+49=48

d)[(-7)-(-4)]×(-8)+(-21)÷(-3)=[-7+4]x(-8)+7 = 24+7=31
2009-09-17T21:40:18+02:00
) [(-2)×10-(-4)×5]×3-14÷(-2)=7
b) (-6)²÷(-4)+3×(-6)-[-(-8)]=-35
c)(16×3)÷(-8)-15÷(-3)+(-7)²=48
d)[(-7)-(-4)]×(-8)+(-21)÷(-3)= 31
Najlepsza Odpowiedź!
2009-09-17T21:41:52+02:00
A) [(-2)×10-(-4)×5]×3-14÷(-2)=(-20+20)*3+7=7
b) (-6)²÷(-4)+3×(-6)-[-(-8)]=36:(-4)-18-8=-9-18-8=-35
c)(16×3)÷(-8)-15÷(-3)+(-7)²=-6+5+49=48
d)[(-7)-(-4)]×(-8)+(-21)÷(-3)= -3*(-8)+7=31